Characterization of Schinopsis haenkeana wood decayed by Phellinus chaquensis (Basidiomycota, Hymenochaetales) - Luna, María Luján (2012)
Schinopsis haenkeana is a native tree to the Chaco Serrano Forests in Argentina.The white-rot fungus Phellinus chaquensis degrades its wood, causing a whiterottype of decay. The objective of this study was to investigate the structuralalterations caused by P. chaquensis in S. hankeana decayed naturally and invitro. Sound living branches with decay and basidiocarps of P. chaquensis weresampled from the field and in vitro decay tests were performed according to theASTM D-2017-81 standard method. Naturally decayed branches exhibited aninnermost discolored zone with white-rot decay and an outer yellowish-whiteportion of sound sapwood. Using LM and SEM, degraded tissue displayed diagnosticcharacters of selective delignification and simultaneous decay. Findingsindicate that P. chaquensis causes a mottled pattern of decay (selective delignificationplus simultaneous decay) in S. haenkeana wood. Other features such asaccumulation of extractives, profuse deposition of crystals and tyloses, typical ofSchinopsis spp. heartwood, were additionally observed. In laboratory degradedmaterial, signs of selective delignification and incipient stages of simultaneousdecay were noticeable only microscopically. Chemical analysis revealed an oxidativealteration of aromatic moieties in naturally decayed samples which mightbe related to the accumulation of phenols as a response to fungal attack whencompared to sound samples. Naturally degraded sapwood exhibits anatomicaland chemical modifications that indicate the development of discolored woodderived from the host-pathogen interaction.